Globally Vibrio cholera antibiotics resistance to RNA and DNA effective antibiotics: A systematic review and meta-analysis. (November 2022) - Rostami, Amirabbas; Zadeh, Firoozeh Abolhasani; Ebrahimzadeh, Farnoosh; Jafari-Sales, Abolfazl; Gholami, Shakiba
Abstract: Background: Vibrio cholera ( V. cholera ) is a facultative pathogen that colonizes the small intestine and produces cholerae toxin as the primary virulence factor that causes cholera and fatal diarrhea in humans. In recent decades, V. cholera has emerged as a notorious multidrug-resistant enteric pathogen. This meta-analysis estimated the pooled proportion of V. cholera antimicrobial resistance against RNA and DNA effective antibiotics. Method: A systematic search was performed for relevant literature until 05 June 2021 in PubMed, Scopus, Embase, and Web of Science databases. Freeman-Tukey double arcsine transformation was performed to estimate weighted pooled resistance (WPR). Results: The meta-analysis were included 164 articles. The WPR of V. cholera were as follows 76% [67, 84] to furazolidone, 65% [29, 94] to nitrofurantoin, 55% [44, 66] to nalidixic acid, 10% [2, 23] to rifampicin, 4%(0, 12) to novobiocin, 4% [2, 6] to norfloxacin, 3% [1, 4] to ciprofloxacin, 1%(0, 3) to sparofloxacin, 0%(0, 3) to levofloxacin, 0%(0, 2) to ofloxacin, 0%(0, 0) to gatifloxacin. Conclusion: V. cholera is a severe problem in Asia and Africa, especially in South Asian countries. The resistance patterns are various in geographical regions. novobiocin 0% (0, 0), and ofloxacin 0% (0, 1) in Africa, gatifloxacin 0% (0, 0), and levofloxacin 0% (0, 6) in Asia and ciprofloxacin 0% (0, 2) in North America are most effective antibiotis. The resistance rate to furazolidone, nalidixic acid, nitrofurantoin, and cephalothin has increased over the years. Monitoring antibiotic resistance and prescribing an appropriate antibiotic is vital to control resistance.